Effect of anisotropic thermal conductivity on thermal control performance of form-stable phase change material. (February 2019) - Huang, Yi-Huan; Cheng, Wen-Long; Han, Bing-Chuan
Abstract: Phase change material (PCM) with anisotropic thermal conductivity can induce heat directional transmission in thermal control of the electronic devices, which improves the thermal control performance. In this paper, a numerical simulation method based on the apparent heat capacity method is proposed to investigate the thermal control performance of the anisotropic form-stable PCM under different heating areas, and the anisotropic form-stable PCM is prepared and a performance test experiment is carried out to validate the accuracy of numerical model. Results show that the experimental results are in good agreement with the simulation results, and the simulation results indicate that the temperature of heat source is reduced rapidly when axial thermal conductivity increases from 1 W/(m∙K) to 5 W/(m∙K). The temperature is also reduced when radial thermal conductivity varies from 1 W/(m∙K) to 30 W/(m∙K) due to the heat diffusion effect along radial direction. The results of the maximum temperature show that the axial thermal conductivity of 5 W/(m∙K) is more appropriate, and the radial thermal conductivity of 30 W/(m∙K) or more is essential for smaller heating area. The results of temperature uniformity indicate that the rational value of anisotropic thermal conductivity should be selected under different situations and requirements.